Effect of Temperature and pH on the Antibacterial Activity of Crab Chitosan - G., Sugumar; A., Selvan; U., Ramesh (Fishery Technology, 2025)
The antibacterial activity of chitosan against Staphxjlococcus aureus and Escherichia coli at 5, 20 and 30oC and at pH 5.0, 5.5, 6.0 and 6.5 was investigated by maintaining the cultures in phosphate buffered saline (PBS) and tryptic soy broth (TSB) with 0.05% chitosan. Temperature had a direct influence on the bactericidal activity of chitosan against both bacteria. Inhibition against S. aureus and E. coli was seen at all temperatures tested with greatest activity at 30oC. The rate of reduction of viable cells of E. coli was slow and complete inhibition could not be obtained at 50C. The antibacterial activity of chitosan was inversely proportional to pH, and there was stronger inhibition at pH